Integrating multiple lines of evidence of sediment quality in a tropical bay (Guanabara Bay, Brazil) - de Campos, Bruno Galvão [UNESP]; Moreira, Lucas Buruaem [UNESP]; Pauly, Guacira de Figueiredo Eufrasio [UNESP]; Cruz, Ana Carolina Feitosa [UNESP]; Monte, Christiane do Nascimento; Dias da Silva, Lílian Irene; Rodrigues, Ana Paula de Castro; Machado, Wilson; Abessa, Denis Moledo de Souza [UNESP] (Elsevier, 2019)
The present study evaluated the ecological risk of metal contamination in sediments of Guanabara Bay (GB) by combining multiple lines of evidence (LOEs). Chemical analysis and a set of whole-sediment toxicity assays were conducted with Tiburonella viscana, Kalliapseudes schubartii, Anomalocardia flexuosa, and Nitocra sp. Results were integrated by multivariate analysis and qualitative methods. Additionally, a whole-sediment Toxicity Identification Evaluation technique (TIE) was applied to identify the chemical groups responsible for the effects. Sediments from harbor and industrial areas exhibited toxicity linked to moderate to high concentrations of Zn, Pb, Cu and Cr. The TIE technique confirmed such effects, but it also indicates the contribution of ammonia and organic compounds to the observed toxicity. Our results demonstrate that the combination of multiple LOEs improves the effectiveness of environmental risk assessment of chemical stressors and management of coastal ecosystems in tropical regions.
Keywords: Bioavailability; Environmental monitoring; Marine pollution; Metals; Sediment toxicity; Toxic identification evaluation (TIE)